ELMOCPAP AND HIGH OXYGEN FLOW THERAPY IN PATIENTS WITH HIV/COVID-19 COINFECTION: CASE REPORT (Cadernos ESP, 2021)
The objective of this study was to report two cases of patients with HIV / COVID-19 coinfection who use ELMOcpap and High Flux Therapy to treat the Severe Acute Respiratory Syndrome (SARS). The reports of cases were performed by review of medical records. Data included were clinical, epidemiological and performance of combined therapy ELMOcpap and TAF. The patients who used non-invasive mechanical ventilation had improved hypoxemia and ventilatory parameters 24h after the beginning of therapy. This is the first study that reported two cases of COVID-19 and HIV coinfection in patients of Brazil who were successful with ELMOCpap and TAF therapy. Thus, combined therapies such as ELMOCpap and TAF are important to manage SARS and can contribute to a shorter hospital stay, as well as prevent complications from the use of invasive mechanical ventilation in these patients.
Keywords: COVID-19; HIV; noninvasive ventilation